Penerapan Model PBL Berbantuan Media Audiovisual pada Materi Perempuan dan Laki-laki sebagai Citra Allah untuk Meningkatkan Hasil Belajar dan Kemandirian Kelas V FASE C SDN 10 Sadok - Liya Kontesa; Yoseph Kristianto; Agustina Susi Indratni (PROSIDING SEMINAR NASIONAL PENDIDIKAN DAN AGAMA, 2024)
This study aims to improve student learning outcomes and independence through the application of the Problem Based Learning (PBL) learning model assisted by audiovisual media on the material "Women and Men as Images of God" in Class V Phase C SDN 10 Sadok. This study uses a classroom action research (CAR) method with two cycles, involving planning, implementation, observation, and reflection. The subjects of the study were 5 class V students. The instruments used included learning outcome tests, independence observation sheets, and interviews. The results showed that the application of the PBL model assisted by audiovisual media significantly improved student learning outcomes, as well as encouraged independence in the learning process. The average value of student learning outcomes increased from the first cycle to the second cycle, as did the independence indicators shown through student activity, responsibility, and independence in solving problems. These findings indicate that the use of the PBL model supported by audiovisual media is effective in developing students' understanding of Catholic Religious Education material as well as critical and independent thinking skills.